Thoughtful hug: an experience of communication during the COVID-19 pandemic (Research, Society and Development, 2022)
The presence of a family member contributes to safety of care, maintains the family bond and plays a vital role in health outcomes. As a precaution to the COVID-19 transmission, the ability to have a relative in the intensive care unit (ICU) was suspended, and the communication between the patient and his family was interrupted. This study aimed to present the experience of the team with a nursing intervention entitled "Virtual Hug", implemented in a Brazilian public hospital ICU. A room was provided where the family could write letters in their own handwriting, deposit them in a box, and then they were read aloud to the patient by health professionals. This communication-focused intervention provided integral, humanized care, and became a tool of emotional support. It reduced the impact produced by disruption in the affective bond due to the need for isolation, corroborating with public policies of humanization and family nursing.